2023
DOI: 10.1093/sysbio/syad022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Host-Switching on the Ecological and Evolutionary Patterns of Parasites

Abstract: Speciation via host-switching is a macroevolutionary process that emerges from a microevolutionary dynamic where individual parasites switch hosts, establish a new association, and reduce reproductive contact with the original parasite lineage. Phylogenetic distance and geographic distribution of the hosts have been shown to be determinants of the capacity and opportunity of the parasite to change hosts. Although speciation via host-switching has been reported in many host-parasite systems, its dynamic on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Our results suggest that host switch plays a more important role in the coevolution process of gyrodactylids and their fish hosts than co-speciation and provides strong support to the previous finding that an adaptive mode of speciation associated with host switch is more prevalent than co-speciation among the gyrodactylids [ 18 ]. This finding also supports the proposal of a recent model study, which suggested that host switch can favor speciation in parasites [ 72 ].
Fig.
…”
Section: Discussionsupporting
confidence: 91%
“…Our results suggest that host switch plays a more important role in the coevolution process of gyrodactylids and their fish hosts than co-speciation and provides strong support to the previous finding that an adaptive mode of speciation associated with host switch is more prevalent than co-speciation among the gyrodactylids [ 18 ]. This finding also supports the proposal of a recent model study, which suggested that host switch can favor speciation in parasites [ 72 ].
Fig.
…”
Section: Discussionsupporting
confidence: 91%
“…(i) The parasite has to establish new associations with the host after transition, and an array of behavioral, physiological, and phenological adaptations are prerequisites to successful adaptations. The hosts' phylogenetic distance determines the parasite's capacity and opportunity to change hosts (D'Bastiani et al, 2023). In our case, each host species, regardless of ground-living or arboricolous, belong to a not very deeply diverging monophyletic lineage called T. unifasciatus group (Prebus, 2017) that may not differ substantially from each other in their life cycle characteristics.…”
Section: Discussionmentioning
confidence: 91%
“…Differential selection and adaptation to different abiotic and biotic environmental factors are often believed to be one of the primary drivers of speciation (Maron et al, 2019;Nosil, 2012). One of the most specific environmental transitions, hostswitching in parasites, has been reported to foster speciation in many host-parasite systems, ascribed to reproductive isolation after establishing a new association with the novel host species (D'Bastiani et al, 2023) and the fact that specific environmental differences may affect genetic traits that trigger speciation processes (Cini et al, 2015;Schluter, 2001). This phenomenon is believed to boost diversity in many specialist herbivores, like gall-inducing plant parasites (Jones et al, 2022;Tilmon & Tilmon, 2008), and parasites (Johnson et al, 2016;Martins et al, 2021), including social parasites (Buschinger, 2009;Lenoir et al, 2001;Savolainen & Deslippe, 1996).…”
Section: Introductionmentioning
confidence: 99%